The Importance of Early Sign Language Acquisition for Deaf Readers. Issue 2 (3rd March 2016) - Clark, M. Diane; Hauser, Peter C.; Miller, Paul; Kargin, Tevhide; Rathmann, Christian; Guldenoglu, Birkan; Kubus, Okan; Spurgeon, Erin; Israel, Erica
Abstract : Researchers have used various theories to explain deaf individuals' reading skills, including the dual route reading theory, the orthographic depth theory, and the early language access theory. This study tested 4 groups of children—hearing with dyslexia, hearing without dyslexia, deaf early signers, and deaf late signers (N = 857)—from 4 countries using both shallow and deep orthographies (American English, Hebrew, German, and Turkish) to evaluate which of these theories best describes variances in deaf children's reading development. Results showed that deaf participants were unlike participants with dyslexia, suggesting that they do not have a phonological processing deficit. Rather, the early language access theory more readily explained the similarities between hearing and deaf early signer participants, stressing the importance of early access to visual language.